On the Stability of Cubic and Quadratic Mapping in Random Normed Spaces under Arbitrary T-Norms - J. Vahidi; S. J. Lee; F. Fallah; R. Ahmadi (Journal of Function Spaces)
We prove the stability of some functional equations in the random normed spaces under arbitrary t-norms.